Optimal inverter-based distributed generation in ULP Way Halim considering harmonic distortion - Sofyan, Sofyan; Faraby, Muhira Dzar; Akhmad, Satriani Said; Gaffar, Ahmad; Fitriati, Andi; Elviralita, Yoan; Muchtar, Akhyar (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Integration of distributed generation (DG) based on the use of new renewable energy is considered to be able to increase the capability of the electric power distribution system. However, the use of inverter-based DG is not optimal, it can worsen the condition of the system, especially in terms of the spread of harmonic distortion which can damage the equipment. This is due to the inverter-based DG technology, apart from supplying electrical energy, DG also injects harmonic currents from existing semiconductor components. This research discusses optimization placement of inverter-based DG using the multi objective particle swarm optimization (MOPSO) method which was tested on the Unit Layanan Pelaksana (ULP) Way Halim 88-bus radial distribution system based on MALTAB 2020b to increase the efficiency of the electrical system by reducing losses and %THDv. The inverter-based DG placed on 24 bus points with a capacity of 690 kW can reduce losses by up to 12.74 kW or 14.96% and all %THDv values for each bus are below 5%.